2012
DOI: 10.1100/2012/381814
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Lateral Interbody Spacers: Going Wider for Going Stiffer

Abstract: This study investigates the biomechanical stability of a large interbody spacer inserted by a lateral approach and compares the biomechanical differences with the more conventional transforaminal interbody fusion (TLIF), with and without supplemental pedicle screw (PS) fixation. Twenty-four L2-L3 functional spinal units (FSUs) were tested with three interbody cage options: (i) 18 mm XLIF cage, (ii) 26 mm XLIF cage, and (iii) 11 mm TLIF cage. Each spacer was tested without supplemental fixation, and with unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 24 publications
2
75
1
Order By: Relevance
“…In addition to indirectly decompressing the neural structures through interbody distraction, Marchi et al have recently published that stand alone lateral interbody fusion was associated with a 91% successful fusion rate (13). In a biomechanical cadaveric study, Pimenta et al have found that a 18 mm extreme lateral interbody cage (XLIF) with unilateral pedicle screw provided greater stability than the 11 mm transforaminal lumbar interbody cage with bilateral pedicle screws (14). Treatment of ASD with LLIF allows for preservation of the anterior and posterior longitudinal ligaments, which preserves stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to indirectly decompressing the neural structures through interbody distraction, Marchi et al have recently published that stand alone lateral interbody fusion was associated with a 91% successful fusion rate (13). In a biomechanical cadaveric study, Pimenta et al have found that a 18 mm extreme lateral interbody cage (XLIF) with unilateral pedicle screw provided greater stability than the 11 mm transforaminal lumbar interbody cage with bilateral pedicle screws (14). Treatment of ASD with LLIF allows for preservation of the anterior and posterior longitudinal ligaments, which preserves stability.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar interbody fusion performed with lateral implants has been shown to be biomechanically superior to other constructions, 4,5 as the larger diameter hollow spacers appear to be favorable for engaging the peripheral margins of the end plate. 6 The good stiffness achieved with lateral wide implants enables standalone constructions to be performed in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a stand-alone construction can provide good stabilization, comparable to a TLIF supplemented with pedicle screws. 4 Good results and complications from non-supplemented LLIF have been reported; [7][8][9][10][11] however, the ideal indication is not clear. Cage settling and vertebral body fracture are potential and significant complications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations